2012
DOI: 10.3892/ijo.2012.1506
|View full text |Cite
|
Sign up to set email alerts
|

Prospective impact of 5-FU in the induction of endoplasmic reticulum stress, modulation of GRP78 expression and autophagy in Sk-Hep1 cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive malignant diseases and is highly resistant to conventional chemotherapy. Therefore, HCC requires more effective prevention and treatment strategies. 5-fluorouracil (5-FU) remains the most widely used chemotherapeutic drug for the treatment of gastrointestinal, breast, head and neck, and ovarian cancers. In pursuit of a novel effective strategy, we have evaluated the potential of 5-FU to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…In this sense, we recently demonstrated that the chemotherapy agent 5FU treatment on colorectal cancer cells significantly increases RHBDD2 mRNA and protein expression, compared with the untreated cells, suggesting that RHBDD2 up-modulation might be induced as an adaptive cellular response to the 5FU cytotoxic effects (Lacunza et al 2012). Interestingly, a recent study showed that 5FU promotes ER stress, activating the mitochondrial apoptotic cell death process (Yadunandam et al 2012). An association of different rhomboid member's genes and the ER quality control process has also been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, we recently demonstrated that the chemotherapy agent 5FU treatment on colorectal cancer cells significantly increases RHBDD2 mRNA and protein expression, compared with the untreated cells, suggesting that RHBDD2 up-modulation might be induced as an adaptive cellular response to the 5FU cytotoxic effects (Lacunza et al 2012). Interestingly, a recent study showed that 5FU promotes ER stress, activating the mitochondrial apoptotic cell death process (Yadunandam et al 2012). An association of different rhomboid member's genes and the ER quality control process has also been established.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we also observed significant RHBDD2 mRNA and protein overexpression in the advanced stages of colorectal cancer (Lacunza et al 2012), suggesting that RHBDD2 up-modulation might be associated with breast and colon cancer malignant progression. We also determined that RHBDD2 protein expression is upregulated in colon cancer cells treated with the chemotherapeutic agent 5-fluourouracil (5FU) (Lacunza et al 2012), which has recently been shown to be an inducer of ER stress in hepatocellular carcinoma cells (Yadunandam et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pgp prevents the accumulation of chemotherapeutic drugs and targeted therapy-agents, determining multidrug resistance (MDR) [8]. Since many chemotherapeutic drugs – such as anthracyclines [9], cisplatin [10], oxaliplatin [9], 5-fluorouracil [11] and paclitaxel [12] – induce a massive ER-stress mediated cell death, the lack of ER stress-dependent apoptotic response coupled with the increased drug efflux strongly reduces the efficacy of these drugs in MDR cells.…”
Section: Introductionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) is an important organe lle which has an important role in protein conformation and post-translational modification, enfoldment and oligomerization (4,5). In addition, ER serves a role in lipid metabolism, steroid hormone synthesis and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Under a variety of conditions (including anoxia, alimentary deficiency, glycosylation, oxidative stress, metabolic disorders and mutant protein expression) cells cause non-folding or misfolding protein aggregation in the ER and result in the expression of the ER stress protein glucose-regulated protein 78 (GRP78). GRP78 is a primary molecular chaperone in the ER and is a member of the heat-shock protein-70 family (5). Multiple stimuli may disturb ER functions and induce GRP78 expression (6), which serves a protective role and enables the survival of tumor cells (7).…”
Section: Introductionmentioning
confidence: 99%